Perancangan Media Interaktif “Mengenal Aksara Jawa” - Citra Ratih Prameswari; Fajar Abadi; Eki Arla Pribadiyanti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The role of computers in the process of teaching and learning activities is very developed. Teachers in schools adapt to using computers as media for deliver learning materials. Javanese script contained in Javanese language subjects is one of the subjects taught to grade 4 elementary school students.The method used in this study is based on interactive media by combining teaching materials, and technological advances. The visual display will contain Javanese script material equipped with images, animations, and audio.Perancangan Media Interaktif “Mengenal Aksara Jawa” is a learning media that adapt students need in this era, so they can easy to receive, absorb, and understand the material.